An assessment of ground subsidence from rock salt mining in Maceió (Northeast Brazil) from 2019 to 2023 using remotely sensed data - Mantovani, José Roberto [UNESP]; Alcântara, Enner [UNESP]; Lima, Thyago Anthony Soares [UNESP]; Simões, Silvio [UNESP] (Elsevier, 2024)
This study investigates ground subsidence in Maceió, the capital of Alagoas, Brazil, utilizing Sentinel-1 Synthetic Aperture Radar (SAR) data from November 2019 to December 2023. Ground subsidence poses significant risks to urban infrastructure and requires comprehensive monitoring and mitigation strategies. We employed the Interferometric Wide Swath (IW) mode of Sentinel-1A, acquiring high-resolution data in descending orbit with VV polarization. Through interferometric processing, including co-registration, phase unwrapping, and coherence estimation, we produced detailed subsidence maps for key neighborhoods such as Bebedouro, Farol, Mutange, Pinheiro, and Bom Parto. Our results reveal that subsidence in Maceió is highly variable across different neighborhoods, with cumulative subsidence reaching up to 3.83 meters in the most affected areas. The Bebedouro neighborhood, for instance, experienced subsidence up to 0.33 meters over an area of 41.85 hectares, while Farol saw significant ground movement impacting 59.49 hectares. The analysis indicates that high-density urban areas are particularly susceptible to subsidence, correlating with increased structural damage and flood vulnerability. The study underscores the importance of integrating geotechnical, urban planning, and environmental management strategies to address subsidence. We recommend the implementation of adaptive urban planning measures and enhanced monitoring techniques using satellite data to mitigate the impact of subsidence on infrastructure and communities. These findings provide a critical foundation for developing resilient urban environments in coastal cities prone to geological and anthropogenic subsidence.
Keywords: Coastal vulnerability; Resilient urban planning; Subsidence; Urban challenges